Genetic and functional analysis of the proteolytic cleavage at the junction of the NS1 and NS2a proteins of murray valley encephalitis virus - Siti Nor Khadijah Addis (Australian national University, 2012)
Flaviviruses are a group of positive-strand RNA viruses of global significance. The flavivirus RNA genome encodes a single open reading frame that is directly translated into a single polyprotein and cleaved by host and virally encoded proteases prior to protein maturation. Hence, the proteolytic cleavage events play a central role in the process of viral gene expression in flaviviruses. Despite the importance of these events, the mechanism of proteolytic cleavage leading to the generation of the two non-structural proteins, NS1 and NS2A is poorly defined.